Readability of Texts: Human Evaluation Versus Computer Index - Heydari, Pooneh; Riazi, A. Mehdi (Mediterranean Journal of Social Sciences, 2012)
This paper reports a study which aimed at exploring if there is any difference between the evaluation of EFL expertreaders and computer-based evaluation of English text difficulty. 43 participants including university EFL instructors andgraduate students read 10 different English passages and completed a Likert-type scale on their perception of the differentcomponents of text difficulty. On the other hand, the same 10 English texts were fed into Word Program and Flesch Readabilityindex of the texts were calculated. Then comparisons were made to see if readers' evaluation of texts were the same or differentfrom the calculated ones. Results of the study revealed significant differences between participants' evaluation of text difficultyand the Flesch Readability index of the texts. Findings also indicated that there was no significant difference between EFLinstructors and graduate students’ evaluation of the text difficulty. The findings of the study imply that while readability formulasare valuable measures for evaluating level of text difficulty, they should be used cautiously. Further research seems necessaryto check the validity of the readability formulas and the findings of the present study.